Kewenangan Komite Stabilitas Sistem Keuangan berdasarkan Pasal 27 Ayat (3) Undang-Undang Nomor 2 Tahun 2020 Dihubungkan dengan Asas Kepastian Hukum - Muhammad Alwan Solahul Khoir; Nurul Chotidjah; Abdul Rohman (UNISBA Press, 2022)
The Financial System Stability Committee or abbreviated as KSSK is a committee that organizes the prevention and resolution of Financial System Crisis to carry out the interests and resilience of the state in the economic sector in Indonesia, which has the following tasks; coordinate in the context of monitoring and maintaining Financial System Stability, handling Financial System Crisis, handling Systemic Bank problems, both in normal Financial System Stability conditions and Financial System Crisis conditions. The aims of this study are: 1) to find out how the position of the Financial System Stability Committee is in issuing State Administrative Decisions, and 2) to find out how the implications of the decisions issued by the KSSK are related to the principle of legal certainty. This study uses a normative juridical approach, namely conducting a study of the rules relating to the Authority of the Financial System Stability Committee. Research specifications by outlining the Authority of the Financial System Stability Committee based on Article 27 Paragraph (3) of Law Number 2 of 2020 concerning State Financial Policy and Financial System Stability for Handling the 2019 Corona Virus Disease Pandemic linked to the principle of legal certainty. Data collection techniques through library research on primary, secondary and tertiary legal materials related to the topic of the problem which will be used as a reference to solve problems as part of data analysis. The results of this study are: 1) the position of the Financial System Stability Committee in issuing State Administrative decisions, namely KSSK is a state administrative body or official or state administration official who is given direct authority by law. 2) the implications of the decisions issued by the KSSK after the existence of Article 27 Paragraph (3) of Law Number 2 of 2020, namely that the decisions issued by the KSSK cannot be filed with the State Administrative Court, where this is not in accordance with the principle of legal certainty. Komite Stabilitas Sistem Keuangan atau disingkat KSSK adalah komite menyelenggarakan pencegahan dan penanganan Krisis Sistem Keuangan untuk melaksanakan kepentingan dan ketahanan negara di bidang perekonomian di Indonesia yang memiliki tugas yaitu; melakukan koordinasi dalam rangka pemantauan dan pemeliharaan Stabilitas Sistem Keuangan, melakukan penanganan Krisis Sistem Keuangan, melakukan penanganan permasalahan Bank Sistemik, baik dalam kondisi Stabilitas Sistem Keuangan normal maupun kondisi Krisis Sistem Keuangan. Tujuan dari penelitian ini yaitu: 1) untuk mengetahui bagaimanakah kedudukan Komite Stabilitas Sistem Keuangan dalam mengeluarkan Keputusan Tata Usaha Negara, dan 2) untuk mengetahui bagaimanakah implikasi dari Keputusan yang dikeluatrkan oleh KSSK dihubungkan dengan Asas Kepastian Hukum. Penelitian ini menggunakan pendekatan yuridis normatif yaitu melakukan kajian terhadap kaidah-kaidah yang berkaitan dengan Kewenangan Komite Stabilitas Sistem Keuangan. Spesifikasi penelitian dengan menguraikan Kewenangan Komite Stabilitas Sistem Keuangan Berdasarkan Pasal 27 Ayat (3) Undang-Undang Nomor 2 Tahun 2020 Tentang Kebijakan Keuangan Negara Dan Stabiilitas Sistem Keuangan Untuk Penanganan Pandemi Corona Virus Disease 2019 Dihubungkan Dengan Asas Kepastian Hukum. Teknik pengumpulan data melalui studi kepustakaan terhadap bahan hukum primer, sekunder dan tertier yang berkaitan dengan topik permasalahan yang nantinya dijadikan rujukan untuk menyelesaikan permasalahan sebagai bagian dari analisis data. Hasil dari penelitian ini yaitu: 1) kedudukan Komite Stabilitas Sistem Keuangan dalam mengeluarkan keputusan Tata Usaha Negara yaitu KSSK merupakan badan atau pejabat tata usaha negara atau pejabat adminsitrasi negara yang diberikan kewenangan langsung oleh Undang-Undang. 2) implikasi dari keputusan yang dikeluarkan KSSK setelah adanya Pasal 27 Ayat (3) Undang-Undang Nomor 2 Tahun 2020 yaitu bahwa keputusan yang dikeluarkan KSSK tidak dapat diajukan gugatan ke Peradilan Tata Usaha Negara, dimana hal tersebut tidak sesuai dengan asas kepastian hukum.